EFFECTS OF SINGLE-SIDED AND CROSS-VENTILATED SLIDING GLASS WINDOW OPENINGS ON THE INDOOR ENVIRONMENT OF A ROOM IN A HOT AND HUMID CLIMATE (Jurnal Teknologi (Sciences & Engineering), 2022)
There are two natural ventilation strategies, namely single-sided and cross ventilation. For a building with a deep layout plan and where cross ventilation is impossible, single-sided ventilation is used. This study aimed to compare the performance of both strategies using sliding glass windows. The method used was field measurement, which was executed in one room of a double-storey detached house. The predicted indoor thermal comfort was calculated using the Adaptive Thermal Comfort index. The main finding from the study agreed with those of previous studies, whereby cross ventilation was found to provide greater indoor airflow than single-sided ventilation. However, with each strategy, indoor thermal comfort could only be achieved only during the morning hours. The findings also show that the wind velocity decreased upon approaching the window opening and reduced further when the indoor space was reached. Another interesting finding is that cross ventilation had the capacity to enhance the indoor air velocity at one of the measurement times. This study is significant as it will stimulate future exploration and investigation of both natural ventilation strategies in hot and humid climates.